2014
DOI: 10.4161/15384101.2014.973324
|View full text |Cite
|
Sign up to set email alerts
|

USP7 controls Chk1 protein stability by direct deubiquitination

Abstract: Chk1, an essential checkpoint kinase in the DNA damage response pathway (DDR), is tightly regulated by both ATRdependent phosphorylation and proteasome-mediated degradation. Here we identify ubiquitin hydrolase USP7 as a novel regulator of Chk1 protein stability. USP7 was shown before to regulate other DDR proteins such as p53, Hdm2 and Claspin, an adaptor protein in the ATR-Chk1 pathway required for Chk1 activation. Depletion or inhibition of USP7 leads to lower Chk1 levels. The decreased Chk1 protein after U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 27 publications
2
48
0
Order By: Relevance
“…Interestingly, a recent study that investigated the function of RAD51AP1 in chicken DT‐40 cells has shown that RAD51AP1 does not only function in the repair of DSBs by homologous recombination, but also plays an important role during unperturbed replication and replication stress . We found that RAD51AP1 interacts with USP7, a DUB that has previously been shown to regulate the stability of Claspin and Chk1 after replication stress . Our finding that RAD51AP1 also interacts with USP7 during replication stress suggests that USP7 might have a general role in deubiquitylating proteins at stalled replication forks and thereby preventing their degradation through the proteasome.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Interestingly, a recent study that investigated the function of RAD51AP1 in chicken DT‐40 cells has shown that RAD51AP1 does not only function in the repair of DSBs by homologous recombination, but also plays an important role during unperturbed replication and replication stress . We found that RAD51AP1 interacts with USP7, a DUB that has previously been shown to regulate the stability of Claspin and Chk1 after replication stress . Our finding that RAD51AP1 also interacts with USP7 during replication stress suggests that USP7 might have a general role in deubiquitylating proteins at stalled replication forks and thereby preventing their degradation through the proteasome.…”
Section: Discussionsupporting
confidence: 64%
“…B and C, Supporting Information Table 2). For instance, we have found that RAD51AP1 interacts with USP7, USP11, and USP1/UAF1 (WDR48) – DUBs that have been previously shown to play an important role in the cellular response to replication stress or DNA damage . Moreover, we have identified the interaction between RAD51AP1 and the ubiquitin ligase HUWE1 as well as the Cul4‐ubiquitin ligase substrate adaptor DDB1‐VPRBP (DCAF1).…”
Section: Resultsmentioning
confidence: 91%
“…USP1 and USP7 are reported to be involved in deubiquitination and stabilization of Chk1 [69, 70]. USP7 was also shown to regulate other DDR proteins such as Claspin, an adaptor protein activated by Chk1 in the ATR–Chk1 pathway [71].…”
Section: Dubs and Genomic Integritymentioning
confidence: 99%
“…It is also worth mentioning that deubiquitinases play a role in determining the stability of both claspin and Chk1. Thus, USP7 and USP29 contribute to determining claspin stability, whereas USP7 was recently shown to antagonize Chk1 ubiquitination . It therefore seems possible that regulation of these deubiquitinase activities might contribute to checkpoint regulation via claspin and Chk1.…”
Section: Chk1 Deactivationmentioning
confidence: 99%